2017
DOI: 10.1007/s11356-017-8541-4
|View full text |Cite
|
Sign up to set email alerts
|

Trace element measurement for assessment of dog food safety

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…However, EU recommendations 68 are for foods with moisture around 12.0%, so in the present study, results were compared to FDA 36 and NRC 37 recommendations because moisture for most recipes evaluated was higher than 65.0%. Another study 35 conducted in Brazil evaluated 95 samples of dry food for dogs and puppies. Concentrations of arsenic, cadmium, and mercury were not considered a risk when compared to maximum safe levels for humans according to Codex Alimentatius 69 , and concentrations of aluminum, antimony, and uranium were considered high according to the same standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, EU recommendations 68 are for foods with moisture around 12.0%, so in the present study, results were compared to FDA 36 and NRC 37 recommendations because moisture for most recipes evaluated was higher than 65.0%. Another study 35 conducted in Brazil evaluated 95 samples of dry food for dogs and puppies. Concentrations of arsenic, cadmium, and mercury were not considered a risk when compared to maximum safe levels for humans according to Codex Alimentatius 69 , and concentrations of aluminum, antimony, and uranium were considered high according to the same standards.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al . 35 evaluated 95 extruded diets for dogs and puppies in Brazil and observed that aluminum, antimony, and uranium were present in some samples above the human maximum permitted levels. The authors also observed that all samples that presented high antimony concentrations contained food coloring.…”
Section: Introductionmentioning
confidence: 99%
“…Duran et al [83] detected heavy metals in commercial pet food samples available in Turkey, although their concentrations appeared to meet the regulated nutritional values by AAFCO. Fernandes et al [18] evaluated ninety-five dry dog foods for puppies and adult dogs in Brazil, whereof the mass fractions for most of the 20 elements determined (including As, Cd, and Hg) were within the permissible limit for dog health. However, Al, Sb, and U were present in some samples above the maximum levels established for humans.…”
Section: Heavy Metals Contentmentioning
confidence: 99%
“…Animal feeds and feed materials may be contaminated with undesirable substances that may come from polluted environments and/or the production process. There are even report documenting the presence of heavy metals in pet food [18][19][20]. Higher levels than normal probably originate from ingredients that have been exposed to environmental pollution and bioaccumulation over time [21].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors of scientific papers deal with the topic of food products' safety for pet animals, assessed from the perspective of their owners [de Nadai Fernandes et al 2018]. According to legal regulations, a product marked as a complete/ maintenance food is balanced in such way that it can be the only source of food for the animal, without leading to nutrient deficiencies [EC 2009].…”
Section: Introductionmentioning
confidence: 99%